Analisis Komparatif Efisiensi Biaya Dan Produktivitas Hidroponik Pada Penggunaan Nutrisi AB Mix Industri Dan Nutrisi Inovasi Kampus - Uray Dian Novita; Dian Sari; Harmoko; Sri Mulyati; Wilis Widi Wilujeng (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
Hydroponics is a soil-less cultivation technique in which the nutrients absorbed by the plants come from AB Mix fertiliser. AB Mix fertiliser contains both macro and micro nutrients. During storage, macro and micro nutrients cannot be combined whilst still in a concentrated state. Over the past four years, the Agribusiness Workshop has innovated by developing AB Mix nutrients, which have been in use since the inception of hydroponic cultivation. Consequently, commercially available industrial AB Mix nutrients have never been utilised at all. The decline in hydroponic vegetable production at the Agribusiness Workshop has prompted an investigation into whether the nutrients currently in use are a contributing factor to this decline. Consequently, a study was conducted to assess the effectiveness, cost-efficiency and significance of using both the commercially available AB Mix nutrient solution and the university’s innovative AB Mix. The research method involved using two different hydroponic modules, with each module dedicated to one of the nutrient solutions, using the same nutrient application rates and the same vegetable varieties. Cost efficiency was then calculated based on the expenditure incurred for purchasing the industrial AB Mix nutrient solution and the cost of producing the university-developed AB Mix nutrient solution. The results showed that the university-developed AB Mix nutrient solution was 29.63 per cent more cost-efficient than the industrial AB Mix nutrient solution. The t-test results indicated that the industrial AB Mix nutrient solution had a greater impact on crop yield.